B292 Continuous spinal for labor analgesia in a patient with hypertrophic cardiomyopathy with high outflow gradient. (11th August 2022) - Brito, S; Ribeiro, S; Almeida, J; Lages, N; Carvalho, M; Machado, H
Abstract : Background and Aims: Pregnant women with hypertrophic cardiomyopathy (HCM) have an increased risk of cardiovascular complications during labor. Particularly when a high outflow gradient is present, tachycardia and systemic vasodilatation are not well tolerated and may lead to cardiac arrest. 1 Methods: A 39-years-old, ASA III, 39-week pregnant woman with HMC was admitted in a tertiary obstetric center for labor induction. HCM was diagnosed two years before following routine electrocardiogram (EKG). At time of delivery patient presented with dyspnea for medium efforts and was taking bisoprolol 2.5mg id. Holter identified occasional polymorphic ventricular extrasystoles. Transthoracic echocardiography reveled asymmetric hypertrophy of ventricular walls with anterior-inferior septal predominance producing high outflow gradient. Global systolic function was preserved. Results: After hemodynamic monitoring including continuous EKG and invasive blood pressure, labor was induced with vaginal misoprostol and continuous spinal analgesia was early performed. A total of Sufentanil 2.5mcg and Ropivacaine 0.2% 5mg were titrated without hemodynamic repercussion and good pain relieve. Vacuum delivery was uneventful. The new born had an Apgar score of 9/10. Mother surveillance and hemodynamic monitoring was maintained during the first 12h of puerperium in an intermediate care unit. Conclusions: To address this case, a multidisciplinary team composed by cardiologists, obstetricians and anesthesiologists was assembled. It was decided to perform a vaginal delivery induction with misoprostol avoiding oxytocin. Vacuum delivery was a strategy to shorten expulsive period. Early and effective labor analgesia with minimal hemodynamic repercussion was key to maintain cardiovascular homeostasis during labor in a patient with symptomatic HCM. Continuous spinal technique was definitely the best option.